Chinese Culture in the 21st Century and its Global Dimensions
XXIII, 216 p. 40 illus.
Keywords: This book investigates the internationalization of Chinese culture in recent decades and the global dimensions of Chinese culture from comparative and interdisciplinary perspectives. It covers a variety of topics concerning the contemporary significance of Chinese culture in its philosophical, literary and artistic manifestations, including literature, film, performing arts, creative media, linguistics, translations and philosophical ideas. The book explores the reception of Chinese culture in different geographic locations and how the global reception of Chinese culture contrasts with the local Chinese community. The chapters collectively cover gender studies and patriarchal domination in Chinese literature in comparison to the world literature, explorations on translation of Chinese culture in the West, Chinese studies as an academic discipline in the West, and Chinese and Hong Kong films and performances in the global context. The book is an excellent resource for both scholars andstudents interested in the development of Chinese culture on the global stage in the 21st Century.